RELIABILITAS KETENTUAN LAHAN FAKTOR PRODUKSI PERTANIAN UU RI NOMOR 5 TAHUN 1960 TENTANG POKOK-POKOK AGRARIA DALAM ZAMAN KONTEMPORER - Manuasa Saragi (to-ra, 2015)
Legislation No.5 Year 1960 about Agrarian promises to treat the land for fulfilling basic need and pros- perity improvement of nationals, and also build nation (energy) power. The State of Indonesia has authority to do many such planning, using and determining the distribution of land for pursuing the greatest wealthy to individually and collectively, and building the nation and state power. Indonesia citizen can have a right to land determined by state regulation or derived from adat law. Factually, the land tends to accumulate in the hand of conglomerates, causes the chance of individually using the sufficient land to be hindered. In this rese- arch, the provisions about farming production factor was researched in legal normative method with question ‘in what extend the provision of production factor of farming in legislation could be realized’. The result of the research, the provision itself not much implementing, one of causes is that the provision not so strong enough for selfcompleting its task. One policy to redistributing land in accordance with more fair manner should be done/considered immediately by government to heal the condition.Kata Kunci: Realibilitas, Ketentuan lahan produksi, Hak perorangan atas tanah; ketentuan faktor produksi pertanian; kemakmuran sebesar-besarnya.